Nitrate Removal from Water Using Electrocoagulation with Activated Carbon: إزالة النترات من المياه بالتخثير الكهربائي مع الكربون المنشط - Soulaiman Bassam Mershed, Bassam Alaji (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2022)
The present work studies the clarification of drinking water by removing Nitrate and Nitrite using electrocoagulation (EC) and the addition of activated carbon which produced from the almond peel (AP). The efficiency of coupling process studied by using different amounts of adsorbent material to identify the most appropriate dosage, for enhancing drinking water purification, The efficiency of the current density used in the removal of Nitrate and Nitrite was studied, energy consumption of the process was also determined. The coupling between electrocoagulation and the addition of the activated carbon showed that the addition of an appropriate dosage resulted in the enhancement of the removal rate of Nitrate and Nitrite especially at lower current densities, and resulted in a considerable reduction in the needed time compared to the conventional process that does not use activated carbon. The electrocoagulation with the addition of activated carbon achieved efficiency removal of approximately 58.5% for Nitrate and 98.9% for Nitrite. Based on the high removal efficiency, short contact time, and low energy consumption, the electrocoagulation with the addition of activated carbon method could be recommended instead of the conventional process. Furthermore, the results suggest that the productivity of the process is enhanced by adding a very small amount of NaCl as a supporting electrolyte.